Effect of Antenatal Counselling on The Uptake of Immediate Postpartum Long Acting Reversible Contraception: A Randomized Controlled Trial At A Tertiary Care Hospital - Mushtaque, Zoya; Rana, Qundeel; Shahid, Ghazia; Sadia, Shamsunnisa (Biological and Clinical Sciences Research Journal, 2025)
Long-acting reversible contraception (LARC) is a highly effective method of family planning, particularly in the immediate postpartum period. However, uptake remains suboptimal due to various systemic and individual barriers. Structured antenatal counseling has been proposed to improve LARC acceptance, but its impact requires further investigation. Objective: To compare the frequency of LARC uptake in the immediate postpartum period among women who received structured antenatal counseling versus those who did not. Additionally, to identify barriers to LARC uptake in both groups. Methodology: This prospective study was conducted at Al-Nafees Medical College and Hospital. Following ethical approval, 160 women meeting the inclusion criteria were randomly assigned to either the intervention group (received at least two structured antenatal counseling sessions) or the control group (no structured counseling). Counseling sessions covered LARC types, benefits, and side effects, with spouse or family participation encouraged. LARC uptake was recorded within 24 hours post-delivery, and barriers to uptake were documented. Data were collected via a structured questionnaire and analyzed using SPSS Version 25. Results: The mean age of participants was 29.73 ± 4.91 years, with a mean inter-pregnancy interval of 20.95 ± 4.25 months. The majority (53.1%) were aged 18-30 years, with 43.1% illiterate and 66.3% homemakers. A combined family system was prevalent (71.3%), and 53.1% lived in urban areas. LARC uptake was 66.9%, highest in the intervention group (70.0%) compared to the control group (63.8%), though the difference was not statistically significant. Common barriers included device unavailability (21.3%) and cost (5.6%). The presence of family during counseling significantly increased LARC acceptance in the control group, while systemic factors like device availability and provider training remained significant obstacles. Conclusion: Structured antenatal counseling improves postpartum LARC uptake, emphasizing its importance in maternal healthcare. Addressing systemic barriers, such as device availability and provider training, alongside routine counseling integration into antenatal care, can enhance contraceptive use and maternal health outcomes. Further large-scale studies are recommended to validate these findings.